GROWTH AND DEVELOPMENT OF BLUEBERRY VARIETIES PLANTS INTRODUCED IN THE CLIMATIC CONDITIONS OF TASHKENT REGION - Choriyevich-Ph.D., Kurbanmuradov Akbar; Choriyevich , Namozov Ikhtiyor (Journal of Medical Genetics and Clinical Biology, 2024)
The duration of the growing season of blueberry varieties, which are introduced into the conditions of the central climate of Uzbekistan, is in the range of 213-221 days. In this case, the shortest period is 213 days in the Toro and Darrou varieties, the longest period is 220-221 days in the Patriot and Legasi varieties, and the duration of the growing season of the remaining varieties is in the range of 215-218 days